Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18805/lr-3823
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and combining ability analysis for yield and yield contributing traits in velvet bean Mucuna pruriens (L.) DC

Abstract: A field experiment was conducted to know the gene action and selection of superior parents of velvet bean for hybridization. The heterosis and combining ability study was carried out using 6x6 half diallel mating design excluding reciprocals. Combining ability analysis revealed that magnitude of sca variance was greater than gca variance suggesting the predominance of non additive gene action for most of the traits except days to 50 per cent flowering, number of flowers per inflorescence, number of pods per bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
2
1
0
Order By: Relevance
“…Eight hybrids were significantly superior by exhibiting significant positive heterosis over check Arka Mangala. Similar findings were reported by Chinapolaiah et al [9] in velvet bean and Khaimichho et al [10] in mung bean. For pod weight, twenty hybrids exhibited significant positive relative heterosis and twelve hybrids exhibited significant and positive heterosis over better parent.…”
Section: Resultssupporting
confidence: 90%
“…Eight hybrids were significantly superior by exhibiting significant positive heterosis over check Arka Mangala. Similar findings were reported by Chinapolaiah et al [9] in velvet bean and Khaimichho et al [10] in mung bean. For pod weight, twenty hybrids exhibited significant positive relative heterosis and twelve hybrids exhibited significant and positive heterosis over better parent.…”
Section: Resultssupporting
confidence: 90%
“…The results on heterobeltiosis corroborated with findings Chinapolaiah et al (2019) who revealed high heterotic effect on plant traits such as days to 50% flowering, pod length, pod weight, dry pod yield per plant and seed yield per plant in velvet bean. Patil et al (2012) revealed high heterosis in crosses of vegetable lab lab bean for number of pods and green pod yield per plant.…”
Section: Seed Yieldsupporting
confidence: 86%
“…The estimation method used(Daxenbichler et al1972) by us in this study is old and laborious; thus, it is plausible that poor recovery and associated short comings might have skewed this experiment. Moderately-high to high heritability (H 2 > 60%) were observed for different traits in our study.Two earlier studies found analogous observation in M. pruriens for traits such as pod length, pod width, pod weight, hundred seed weight, seed yield per plant, and in orescence length(Hadapad et al 2018;Chinapolaiah et al 2019). Our results reinforce them.…”
mentioning
confidence: 56%